Perception of St. Valentine’s Day in the Culture Space of Latvia - Kovzele, Oksana (Technium Social Sciences Journal, 2021)
Under the contemporary social and economic conditions, no culture can stay “sterile”. Growth of Internet communication and globalization processes facilitates borrowing of new realia including festivities and festive traditions and their circulation in the global culture environment. One of such realia that has become extremely widespread in Europe and the whole world is St. Valentine’s Day. Recent research literature regards it in various aspects (psychological, feminist, commercial, etc.); researchers are also interested in the experience of celebrating St. Valentine’s Day in diverse regions and countries. The present paper aims at characterizing the specificity of perceiving St. Valentine’s Day in Latvia on the basis of newspaper, magazine, almanac articles available to readers in the course of 70 years (since the 1950s till nowadays). On the basis of article content analysis, the paper marks the trends characteristic of Latvian society in treatment of St. Valentine’s Day under different historical, political, and economic conditions, Latvians being in their homeland and/or in exile. The compiled materials show that St. Valentine’s Day entered Latvian culture space and got rooted there only after regaining state independence – in the 1990s and especially in the 21st century. Nowadays it is represented in various spheres of public life, yet the residents’ reaction to this phenomenon that is still foreign to many is rather ambiguous. St. Valentine’s Day is not only associated with love and romance but is treated as a tool that yields commercial profit for traders, whereas for others it causes needless expenses, depression, and disappointment.